2012
DOI: 10.1186/gb-2012-13-3-r20
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of plant nat-siRNAs reveals insights into their distribution, biogenesis and function

Abstract: BackgroundMany eukaryotic genomes encode cis-natural antisense transcripts (cis-NATs). Sense and antisense transcripts may form double-stranded RNAs that are processed by the RNA interference machinery into small interfering RNAs (siRNAs). A few so-called nat-siRNAs have been reported in plants, mammals, Drosophila, and yeasts. However, many questions remain regarding the features and biogenesis of nat-siRNAs.ResultsThrough deep sequencing, we identified more than 17,000 unique siRNAs corresponding to cis-NATs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
156
3
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(185 citation statements)
references
References 77 publications
11
156
3
5
Order By: Relevance
“…Thus, one may expect that cellular sRNAs map to cis-NATs at high frequencies. Consistent with this idea, Zhang et al (2012) recently reported that siRNAs are overrepresented (P , 0.04) among the 39 UTRs of cis-NATs compared with 39 UTRs of non-cis-NATs (Zhang et al, 2012). In contrast, Henz et al (2007) found that sRNAs are more enriched in non-cis-NATs compared with cisNATs (Henz et al, 2007).…”
Section: Patterns Of Cis-nat Abundances Are Likely Due To Transcriptisupporting
confidence: 51%
See 3 more Smart Citations
“…Thus, one may expect that cellular sRNAs map to cis-NATs at high frequencies. Consistent with this idea, Zhang et al (2012) recently reported that siRNAs are overrepresented (P , 0.04) among the 39 UTRs of cis-NATs compared with 39 UTRs of non-cis-NATs (Zhang et al, 2012). In contrast, Henz et al (2007) found that sRNAs are more enriched in non-cis-NATs compared with cisNATs (Henz et al, 2007).…”
Section: Patterns Of Cis-nat Abundances Are Likely Due To Transcriptisupporting
confidence: 51%
“…Across all genotypes, sRNAs matched PC non-cis-NATs from 1.4-to 5.2-fold more frequently than PC cis-NATs (Table IV). The frequency with which an sRNA sequenced from a putative nat-siRNA biogenesis mutant (dcl1, dcl2, dcl3, rdr2, rdr6; Borsani et al, 2005;Zhang et al, 2012) matched a PC cis-NAT was similar to the frequency with which an sRNA sequenced from wild-type plants and other sRNA mutants (dcl4, rdr1; Xie et al, 2004Xie et al, , 2005 matched PC cis-NATs (Table IV).…”
Section: Evidence For the Transcriptional Regulation Of Cis-natsmentioning
confidence: 86%
See 2 more Smart Citations
“…The genome loci of cis-NAT were referred to the previous study results (Jin et al 2008; Zhang et al 2012). Blast was used to match the sRNA to these loci.…”
Section: Methodsmentioning
confidence: 99%